PERJALANAN SENIMAN DI DUNIA VIRTUAL MELALUI E-GOVERNMENT - may yusita sari sita; Bagoes Soenarjanto; Dida Rahmadanik (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
The virtual era requires artists to be more developed in their work and also be able to apply their work to virtual media. UPT Taman Budaya as a place where artists show their existence which will later be uploaded through the YouTube account of UPT Taman Budaya, namely Cak Durationm, in this case UPT Taman Budaya helps artists to continue to develop through virtual event performances in the Cak Duration building. By using direct observation techniques in the field, the author is assisted by employees. The author as an internship student at UPT Taman Budaya participates in helping virtual event activities during the internship, and the author also provides suggestions and solutions to promote the virtual event through promotional advertisements on social media belonging to UPT Taman Budaya